2007
DOI: 10.1073/pnas.0702138104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nematode mechanics by piezoresistive displacement clamp

Abstract: Studying animal mechanics is critical for understanding how signals in the neuromuscular system give rise to behavior and how force-sensing organs and sensory neurons work. Few techniques exist to provide forces and displacements appropriate for such studies. To address this technological gap, we developed a metrology using piezoresistive cantilevers as force-displacement sensors coupled to a feedback system to apply and maintain defined load profiles to micrometer-scale animals. We show that this system can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
164
7
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 147 publications
(201 citation statements)
references
References 41 publications
27
164
7
1
Order By: Relevance
“…the local material properties of the worm have confirmed that Dpy worms exhibit an~25% softer cuticle (19), consistent with a significant disruption of cuticle structure. However, we found that both dpy-5 and dpy-10 worms exhibited no significant difference in their bulk modulus compared with wild-type worms (Fig.…”
Section: Biophysical Journal 108(8) 1887-1898mentioning
confidence: 65%
See 4 more Smart Citations
“…the local material properties of the worm have confirmed that Dpy worms exhibit an~25% softer cuticle (19), consistent with a significant disruption of cuticle structure. However, we found that both dpy-5 and dpy-10 worms exhibited no significant difference in their bulk modulus compared with wild-type worms (Fig.…”
Section: Biophysical Journal 108(8) 1887-1898mentioning
confidence: 65%
“…Because the worm is approximately radially symmetric, we treat the worm as a cylinder (14,19,37) and estimate changes in the body volume from its area and the length, using VðpÞ ¼ ðp=4ÞA 2 ðpÞ=LðpÞ:…”
Section: Bmentioning
confidence: 99%
See 3 more Smart Citations